Betram Windle : the Honan Bequest and the Modernisation of University College Cork, 1904-1919 - Keogh, Ann (Book collections on Project MUSE., 2010)
Bertram Windle, given his background and formation, provides a unique view of Irish politics, history and education. The work is all the more important because of the richness of primary sources on which it is based.